Production and added value of waste cooking oil product derivatives in the Bali Province - Dewa Ayu Anom Yuarini; Ganda Putra; AAPA Suryawan Wiranatha; Luh Putu Wrasiati (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Waste cooking oil or waste cooking oil (WCO) is the remaining oil (or by-products) produced during food frying. In 2019, the cooking oil consumption in Bali Province was 4,735,057 L/month and the WCO produced was estimated about 3,314,540 L/month. The Government of Bali plans to manage WCO in an integrated manner WCO in an integrated manner by processing it as derivative products with economic value. The study aimed to transform WCO into high-value added products (i.e. aromatherapy candles, liquid soap, and biodiesel), and to analyze their economy valued added. The Hayami method was used to determine the economyvalue added of each product. The results showed that WCO was most widely used in producing biodiesel (84%), candle (17%), and liquid soap (10%). Based on the Hayami method, the added value from candle products was IDR. 4,838 / kg (or added value ratio of 9.68%), was classified as a low added product. The added value of liquid soap was IDR 8,495/kg (or added value ratio of 47.38%), classified as a high added value product. While, biodiesel products generating the added value of IDR 2,363/kg (or added value ratio of 25.57%), classified as a medium added value product.